Vibrational analysis of deoxy-andrographolide using MM/QM methods. Issue 5 (2007) - Singh Singh, P. K. P. K.; Hasan Hasan, Tanveer Tanveer; Prasad Prasad, Onkar Onkar; Sinha Sinha, Leena Leena; Jain Jain, Sudha Sudha; Raj Raj, Kanwal Kanwal; Sundaraganesan Sundaraganesan, N. N.; Misra Misra, Neeraj Neeraj
Abstract : Bioactive natural products have an enormous economic importance as speciality chemicals. Extracts of the shrub Andrographis paniculata are widely used as herbal medicines in many countries. Diterpenoid lactones isolated from these extracts have been the subject of extensive investigation, and one of its constituent diterpenoid is deoxy-andrographolide. A complete normal coordinate analysis was performed for deo-andrographolide in terms of the calculation by using Classical mechanics and Quantum mechanical methods.The study of vibrational spectra helps in understanding the dynamical behaviour and hence a lot of information can be derived about the conformation. The geometrical parameters and the vibrational spectra have been discussed in detail.